2014
DOI: 10.1111/nmo.12481
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antireflux treatment on the frequency of awakenings from sleep in patients with Gastroesophageal reflux disease

Abstract: While esomeprazole significantly reduced esophageal acid exposure during conscious awakenings and recumbent-awake and asleep periods, it did not decrease the number and duration of conscious awakening or duration of recumbent-awake period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Pantoprazole for 1.4 months improved all sleep disturbances in more than 75% of patients and resolved nGER symptoms . Interestingly, in a study using 24‐h esophageal pH testing with actigraphy, esomeprazole 40 mg once daily improved esophageal acid exposure during the recumbent awake, recumbent asleep, and conscious awakening periods; however, it did not improve objective sleep parameters, such as duration of recumbent awakening or frequency of conscious awakenings . In such refractory cases, using PPIs before dinner once daily or using PPIs twice daily would be effective in improving objective sleep parameters.…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pantoprazole for 1.4 months improved all sleep disturbances in more than 75% of patients and resolved nGER symptoms . Interestingly, in a study using 24‐h esophageal pH testing with actigraphy, esomeprazole 40 mg once daily improved esophageal acid exposure during the recumbent awake, recumbent asleep, and conscious awakening periods; however, it did not improve objective sleep parameters, such as duration of recumbent awakening or frequency of conscious awakenings . In such refractory cases, using PPIs before dinner once daily or using PPIs twice daily would be effective in improving objective sleep parameters.…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
“…50 Interestingly, in a study using 24-h esophageal pH testing with actigraphy, esomeprazole 40 mg once daily improved esophageal acid exposure during the recumbent awake, recumbent asleep, and conscious awakening periods; however, it did not improve objective sleep parameters, such as duration of recumbent awakening or frequency of conscious awakenings. 60 In such refractory cases, using PPIs before dinner once daily or using PPIs twice daily would be effective in improving objective sleep parameters. Using PPI before dinner rather than before breakfast might have more effectively controlled the reflux-related awakenings during sleep.…”
Section: Effect Of Reflux Treatment On Sleepmentioning
confidence: 99%
“…Persistent GERD symptoms may also lead to sleep deprivation, lower quality of life, and decreased work productivity [ 4 6 ]. In fact, more than 50% of GERD patients experience heartburn when awake [ 7 ], and nighttime reflux causes sleep disorders [ 4 ]. Therefore, it is important to diagnose and treat GERD before it progresses.…”
Section: Introductionmentioning
confidence: 99%
“…Orr et al also used polysomnography to determine the effects of rabeprazole treatment and found that such treatment improved sleep quality (10). Meanwhile, Chand et al reported that the administration of esomeprazole was not associated with sleep efficiency (11) and Jha et al also reported that esomeprazole had no impact on the duration of the recumbentawake period and the frequency or duration of awakening to a conscious states in GERD patients (12). The reasons for these discrepancies in previous studies are unknown.…”
mentioning
confidence: 99%
“…Jha et al also reported that a subgroup exhibiting nonerosive reflux disease (NERD) with regurgitation had a significantly higher rate of impaired daily activity than a subgroup exhibiting erosive esophagitis with regurgitation particularly, regarding eating or drinking problems and work interference (12). In Japan, patients with NERD as well as erosive esophagitis were also reported to be affected by sleep impairment (1, 2).…”
mentioning
confidence: 99%